Physical stature in nineteenth-century new zealand: A preliminary interpretation - Inwood, K.; Oxley, Leslie; Roberts, E. (2010)
During the late nineteenth century, the physical stature of New Zealand-born men stagnated, despite an apparently beneficial public health environment and growth in per-capita incomes. We examine trends and differentials in male stature through World War I enlistment and casualty records. Stature varied by social class, with professionals and men in rural occupations substantially taller than their peers. There is not enough evidence to show that the indigenous Maori population differed in height from men of European descent. Stagnation in stature in late nineteenth-century New Zealand is consistent with patterns observed in Australia, North America, and Western Europe. © 2010 The Authors. Australian Economic History Review© Blackwell Publishing Asia Pty Ltd and the Economic History Society of Australia and New Zealand 2010.